Review on Deep Learning, Machine Learning and its Application (International Journal of Innovative Research in Computer Science & Technology, 2020)
In contemporary computer sciences, machine  learning is one of the areas. To make machines intelligent, a  lot of study has been done. Learning is a fundamental aspect  of both computer and human behavior. For the same  problem, many techniques have been created in a variety of  sectors of operation. Machine learning techniques that are  more traditional have indeed been developed. Researchers  have worked hard to develop the exactness of these learning  algorithms. They have thought of another level contributing  to a broad definition of learning. Deep study is a machine  learning subset. Few deep learning implementations have  been researched until now. This would undoubtedly resolve  concerns in many new areas of application, sub-domains that  use profound learning. This paper illustrates a study of  historical and future areas, sub-domains and  implementations for computer learning and learning.
Keywords: Applications; Computer; Deep Learning; Machine Learning